2018
DOI: 10.18517/ijaseit.8.3.2756
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining for Detecting E-learning Courses Anomalies: An Application of Decision Tree Algorithm

Abstract: E-learning adaptation has become the most important method that facilitates access to the appropriate content. Adaptive approaches consist of reducing the problems of incompatibilities between learner's cognitive abilities and educational content's difficulties. In some cases, the adapted curriculum cannot meet learner's skills completely seen its incoherent structure, its unsuitable methodologies and sometimes its complexity. Therefore, we need to measure the convenience of the content material to improve it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…An example how data mining has been used to predict rainfall has been shown in [5,6,7]. Beside prediction task, data mining has been used to detect e-learning courses anomalies as explored in [8].…”
Section: Introductionmentioning
confidence: 99%
“…An example how data mining has been used to predict rainfall has been shown in [5,6,7]. Beside prediction task, data mining has been used to detect e-learning courses anomalies as explored in [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are many previous studies that adopted the use of Naive Bayesian Classifier algorithm for the classification texts and documents. Also, the studies' results indicated that obtained classified materials have a high accuracy and the algorithm had the ability to work in a way that surpasses the most advanced classification models such as boosted trees or random forests models (e.g., [20], [19]- [31]) classifying learning materials based on Decision Tree algorithm [32]. However, a comparison between our work and previous mentioned research is not valid as they have been used in different contexts.…”
Section: Resultsmentioning
confidence: 69%
“…e latter analyzes the health, social activity, relationships, and academic performance, most related to and affect the performance of students. e convenience content material for learners is also predicted by decision trees [24].…”
Section: Introductionmentioning
confidence: 99%